Transcriptional Landscape of Ectomycorrhizal Fungi and Their Host Provides Insight into N Uptake from Forest Soil - Rivera Pérez, Carmen Alicia; Janz, Dennis; Schneider, Dominik; Daniel, Rolf; Polle, Andrea (mSystems, 2022)
Although EMF are well known for their role in supporting tree N nutrition, the molecular mechanisms underlying N flux from the soil solution into the host through the ectomycorrhizal pathway remain widely unknown. Furthermore, ammonium and nitrate availability in the soil solution is subject to frequent oscillations that create a dynamic environment for the tree roots and associated microbes during N acquisition. Mineral nitrogen (N) is a major nutrient showing strong fluctuations in the environment due to anthropogenic activities. The acquisition and translocation of N to forest trees are achieved mainly by highly diverse ectomycorrhizal fungi (EMF) living in symbioses with their host roots. Here, we examined colonized root tips to characterize the entire root-associated fungal community by DNA metabarcoding-Illumina sequencing of the fungal internal transcribed spacer 2 (ITS2) molecular marker and used RNA sequencing to target metabolically active fungi and the plant transcriptome after N application. The study was conducted with beech ( Fagus sylvatica L.), a dominant tree species in central Europe, grown in native forest soil. We demonstrate strong enrichment of 15 N from nitrate or ammonium in the ectomycorrhizal roots by stable-isotope labeling. The relative abundance of the EMF members in the fungal community was correlated with their transcriptional abundances. The fungal metatranscriptome covered Kyoto Encyclopedia of Genes and Genomes (KEGG) and Eukaryotic Orthologous Groups (KOG) categories similar to those of model fungi and did not reveal significant changes related to N metabolization but revealed species-specific transcription patterns, supporting trait stability. In contrast to the resistance of the fungal metatranscriptome, the transcriptome of the host exhibited dedicated nitrate- or ammonium-responsive changes with the upregulation of transporters and enzymes required for nitrate reduction and a drastic enhancement of glutamine synthetase transcript levels, indicating the channeling of ammonium into the pathway for plant protein biosynthesis. Our results support that naturally assembled fungal communities living in association with the tree roots buffer nutritional signals in their own metabolism but do not shield plants from high environmental N levels. IMPORTANCE Although EMF are well known for their role in supporting tree N nutrition, the molecular mechanisms underlying N flux from the soil solution into the host through the ectomycorrhizal pathway remain widely unknown. Furthermore, ammonium and nitrate availability in the soil solution is subject to frequent oscillations that create a dynamic environment for the tree roots and associated microbes during N acquisition. Therefore, it is important to understand how root-associated mycobiomes and the tree roots handle these fluctuations. We studied the responses of the symbiotic partners by screening their transcriptomes after a sudden environmental flux of nitrate or ammonium. We show that the fungi and the host respond asynchronously, with the fungi displaying resistance to increased nitrate or ammonium and the host dynamically metabolizing the supplied N sources. This study provides insights into the molecular mechanisms of the symbiotic partners operating under N enrichment in a multidimensional symbiotic system.